2009
DOI: 10.1175/2009wcas1009.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Interdependencies and Human Cooperation: The Process of Adapting to Droughts

Abstract: The Bear River Basin, which includes portions of Idaho, Utah, and Wyoming in the United States, has a dynamic history of human hydrologic adaptations in relation to a highly variable water supply. These adaptations are embedded in a geographical setting highly influenced by the legal, policy, and institutional contexts that govern allocation of water in this generally arid region. In response to several years of drought and a historically low water year in 2004, water users in the Bear River Basin tested the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…A number of recent case studies that highlight local water managers' identified strategies and barriers in adapting to climate-induced water supply variability compare well with our case study findings [29,31,36,45,[88][89][90]. In the Wasatch Range of northern Utah, for example, water managers described challenges with enhancing water supply to meet growing population demand, obtaining funds to build and restore aging infrastructure, and coordinating diverse water use interests [31].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…A number of recent case studies that highlight local water managers' identified strategies and barriers in adapting to climate-induced water supply variability compare well with our case study findings [29,31,36,45,[88][89][90]. In the Wasatch Range of northern Utah, for example, water managers described challenges with enhancing water supply to meet growing population demand, obtaining funds to build and restore aging infrastructure, and coordinating diverse water use interests [31].…”
Section: Discussionsupporting
confidence: 77%
“…Mutual recognition of their interdependent water uses motivated adaptation to 2004 drought conditions among water users in the Bear River Basin of Idaho, Utah, and Wyoming. This recognition led to cooperative and innovative strategies involving water settlement agreements, science-based information sharing, and hydrologic and river operations modeling [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brooks and Adger (2004) explain that a society's adaptive capacity depends on the ability of its people to act collectively and resolve conflicts. Endter-Wada et al (2009) conducted an in-depth case study that described the unfolding history of how people in the Bear River Basin have learned to cooperate and increase their adaptive capacity in times of drought. They found that conflict and cooperation over water resources constantly evolves, based on people's ways of knowing water and each other.…”
Section: The Bear River Basin As a Social-ecological Systemmentioning
confidence: 99%
“…Collaboration in AM, through knowledge sharing and collective action among users who are interdependent on common resources, increases learning by bringing multiple perspectives to bear on the same problem, thereby decreasing uncertainty and increasing adaptive capacity (Olsson et al 2004, Hahn et al 2006, Endter-Wada et al 2009). However, collaboration becomes more challenging as population growth increases the number of parties in collaborative processes and climate change tightens the linkages in SESs by shortening the response time between changes in ecological components and reactions in social components (and vice versa;Walker et al 2002, Folke 2006.…”
Section: Box 1 Prior Appropriation Water Law Terminologymentioning
confidence: 99%